2010
DOI: 10.2214/ajr.10.4192
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Ablation of Spinal Osteoid Osteomas Close to Neural Elements: Technical Considerations

Abstract: Percutaneous thermal ablation can be used to manage spinal osteoid osteomas close to the neural elements. Special thermal protection techniques may add a margin of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 23 publications
0
67
0
5
Order By: Relevance
“…Due to the proximity to nervous structures, treating osteoid osteomas near the spinal column constitutes a special situation. However, multiple studies have shown that RFA is also a safe method of therapy for spinal osteoid osteomas [37,38]. Both studies achieved absence of pain in 79 % of cases following initial RFA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the proximity to nervous structures, treating osteoid osteomas near the spinal column constitutes a special situation. However, multiple studies have shown that RFA is also a safe method of therapy for spinal osteoid osteomas [37,38]. Both studies achieved absence of pain in 79 % of cases following initial RFA.…”
mentioning
confidence: 99%
“…Both studies achieved absence of pain in 79 % of cases following initial RFA. Nervous structures can be isolated and cooled using air or carbon dioxide (CO2), or can alternatively be displaced with glucose or sterile water [37]. If the space-occupying aspect of the osteoid osteoma results in a compression of the nerve root, then surgery is indicated for the osteoid osteoma [38].…”
mentioning
confidence: 99%
“…Other percutaneous techniques have been proposed, such as laser thermal therapy, cryotherapy, and ethanol therapy [1,2,26,27]. CT-guided RFA has become the preferred method owing to a low morbidity rate, minimal postoperative complications, minimal tissue exposure, rapid recovery, and no restriction of weightbearing activity [10,14,33,50,60,69]. In addition, the healing rate is 76% to 100% [14,53], with a major complication rate of 0% to 5% [2,6,45].…”
Section: Discussionmentioning
confidence: 99%
“…3 In some RF ablation, laser ablation, and cryoablation procedures with posterior wall destruction, gases injected into the spinal canal successfully displaced and insulated the spinal cord, preventing neurological damage. 4 Interstitial ultrasound ablation may have advantages over other ablation modalities in settings involving bone. Unlike RF ablation, laser ablation, and cryoablation, interstitial ultrasound can be applied with directional control of heat deposition along the length and circumference of the applicator, and it can take advantage of the preferential heating that occurs along bone surfaces due to high ultrasound absorption.…”
Section: Introductionmentioning
confidence: 99%